MAIN STAGES OF THE LIFE CYCLE OF THE REPLACING FAMILY: MODELING AND CONTENT FILLING - L. Saenko; G. Solomatina (Вестник Северо-Кавказского федерального университета)
The article discusses the key stages of the life of a substitute family. The authors proposed the main stages that each substitute family lives. Considerable attention is paid to the substantive content of each stage. The roles of foster parents and adopted children at each stage are disclosed. The article sets out the views on how the life cycles of a substitute and an ordinary family differ. Particular attention is paid to the adaptation stage, since it depends on the positive course of this stage whether the remaining stages will take place or whether the child will be returned to the social institution.